Synthesis of large low-redundancy linear arrays. - Camps, A. (IEEE Transactions on antennas and propagation)
Aperture synthesis interferometric radiometers can overcome mass, weight and mechanical scan limitations of present-day radiometers. A full antenna array is "thinned" by eliminating selected antennas, while keeping all possible antenna separations. This paper describes a new technique for the direct synthesis of low-redundancy large arrays, consisting in growing small arrays by inserting a seed repeatedly. This technique has achieved the largest thinned arrays with the least redundancy reported in the literature